Homeostatic Response to Three Years of Experimental Warming Suggests High Intrinsic Natural Resistance in the Páramos to Warming in the Short Term - Lasso, Eloisa; Matheus-Arbeláez, Paola; Gallery, Rachel E.; Garzón-López, Carol; Cruz, Marisol; Leon-Garcia, Indira V.; Aragón, Lina; Ayarza-Páez, Alejandra; Curiel Yuste, Jorge (Frontiers in Ecology and Evolution, 2021)
Páramos, tropical alpine ecosystems, host one of the world´s most diverse alpine floras, account for the largest water reservoirs in the Andes, and some of the largest soil carbon pools worldwide. It is of global importance to understand the future of this extremely carbon-rich ecosystem in a warmer world and its role on global climate feedbacks. This study presents the result of the first in situ warming experiment in two Colombian páramos using Open-Top Chambers. We evaluated the response to warming of several ecosystem carbon balance-related processes, including decomposition, soil respiration, photosynthesis, plant productivity and vegetation structure after three years of warming. We found that OTCs are an efficient warming method in the páramo, increasing mean air temperature by 1.7 oC and mean daytime temperature by 3.4 oC. The maximum air temperature differences between OTC and control was 23.1 oC. Soil temperature increased only by 0.1oC. After three years of warming using 20 OTC (10 per páramo) in a randomized block design, we found no evidence that warming increased CO2 emissions from soil respiration, nor did it increase decomposition rate, photosynthesis or productivity in the two páramos studied. However, total C and N in the soil and vegetation structure are slowly changing as result of warming and changes are site dependent. In Sumapaz, shrubs and graminoids cover increased in response to warming while in Matarredonda we observed an increase in lichen cover. Whether this change in vegetation might influence the carbon sequestration potential of the páramo needs to be further evaluated. Our results suggest that páramos ecosystems can resist an increase in temperature with no significant alteration of ecosystem carbon balance related processes in the short term. However, the long-term effect of warming could depend on the vegetation changes and how these changes alter the microbial soil composition and soil processes. The differential response among páramos suggest that the response to warming could be highly dependent on the initial conditions and therefore we urgently need more warming experiments in páramos to understand how specific site characteristics will affect their response to warming and their role in global climate feedbacks.